Potential Osteoinductive Effects of Calcitriol on the m-RNA of Mesenchymal Stem Cells Derived from Human Alveolar Periosteum - Hong, Hsiang-Hsi (Biomed Res Int, 2016)
This study characterized alveolar periosteum-derived mesenchymal stem cells (P-MSCs) and examined the hypothesis that 1,25-(OH)(2)D(3) (calcitriol) exerts osteoinductive effects on P-MSCs. The mRNA expressions of alkaline phosphatase (ALP), bone sialoprotein (BSP), core-binding factor alpha-1 (CBFA1), collagen-1 (Col-1), osteocalcin (OCN), and vitamin D(3) receptor (VDR) were assessed after incubation with calcitriol for 2 weeks. Vitamin C as positive control (Vit. C-p) increased ALP and CBFA1 mRNA expression at both 1 and 2 weeks and increased BSP and Col-1 mRNA expression only at the first week. A concentration of 10(−8) M calcitriol enhanced ALP, CBFA1, Col-1, and OCN mRNA expression at both weeks and BSP mRNA expression at the first week. Furthermore, 10(−7) M calcitriol increased the mRNA expressions of all compounds at both weeks, except that of CBFA1 at the first week. 10(−8) M calcitriol and Vit. C-p enhanced ALP activity at the second and third weeks. The results revealed that 10(−9), 10(−8), and 10(−7) M calcitriol induced osteoinduction in alveolar P-MSCs by increasing ALP, CBFA1, Col-1, and OCN mRNA expression. A 10(−7) M calcitriol yielded a higher mRNA expression than Vit. Cp on VDR and OCN mRNA expression at both weeks and on Col-1 mRNA at the second week.